ANALYSIS OF ß-CASEIN GENE FOR A1 AND A2 GENOTYPE USING ALLELE SPECIFIC PCR IN KANGEYAM AND HOLSTEIN FRIESIAN CROSSBRED CATTLE IN TAMIL NADU - M. Malarmathi; T. M. A. Senthil Kumar; M. Parthiban; T. Muthuramalingam; A. Palanisammi (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Milk is the one of the most important protein diet to the human population. However, in last few decades, presence of A1 b casein in milk was associated with important issues associated with range of illnesses in human being. In this study a total of 85 cattle blood samples (Kangeyam and HF crossbred) were analysed for A1 b casein gene based on AS-PCR. A1/A2 genotype frequency data indicated that 37% were A2 homozygous (A2A2), 17% were A1 homozygous (A1A1) and 46% heterozygous (A1A2) in HF cross bred cattle. The pure Kangeyam (Bos indicus) cattle breed had only A2 gene and showed only A2A2 genotype, which produce safer A2 milk for the human consumption. The Holstein Friesian cross breed animal also showed mostly of A2 gene (0.595).